The Evaluation of Implementing Digital Pedagogy to Teach English for Aviation - Gracia Nurika Purwanti; Frimadhona Syafri; Dwi Rukmini (English Education Journal, 2022)
English is the primary language of communication in the aviation industry. Aviation English is a subset of English for Special Purposes (ESP) that applies to all air traffic controllers and anyone interested in aeronautics or aviation. However, it is more difficult because most pilots and crew members do not speak English as their first language. The researcher discovered that English is still a barrier for students to reach the criteria necessary for graduates of the Faculty of Aerospace Technology based on preliminary investigations conducted at the Institut Teknologi Dirgantara Adisutjipto (ITDA) Yogyakarta. To evaluate the extent to which teachers implement digital and pedagogical techniques with their students, the researcher utilized a methodology named TPACK The design of this research was a form of qualitative research: a case study. The instruments were questionnaires, observation checklists, and interview questions. Based on the finding, the writer concludes that the ITDA Yogyakarta lecturers can implement the technology in digital pedagogy to teach the English language for Aviation.